Crecimiento de las empresas industriales influenciado por la gestión organizacional y administrativa en la Región Callao, Perú, 2022 - Cuzcano Rivas, Juan Abilio (2022)
Conferencia en la 2nd LACCEI International Multiconference on Entrepreneurship, Innovation and Regional Development - LEIRD 2022: “Exponential Technologies and Global Challenges: Moving toward a new culture of entrepreneurship and innovation for sustainable”, Virtual Edition, December 5 – 7.